Struggling to reply to reviewers: Some advice for novice researchers - Harvey, Orlanda; Taylor, Alison; Regmi, Pramod R; van Teijlingen, Edwin (Health Prospect, 2022)
Peer review is key in academic publishing, and rejection (or at least being asked to resubmit your paper to the journal), is a not uncommon occurrence. However, receiving such rejection and having to reply to it can be hard for the early-career researcher. In this paper, we first highlight the role of the peer reviewer, followed by some of the less friendly reviewers’ comments to our own submitted papers in four case studies. We conclude with several suggestions of ways to deal with less than positive reviews.